2003
DOI: 10.1002/food.200390021
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of peppermint and sweet basil essential oils and their major aroma constituents on some plant pathogenic fungi from the vapor phase

Abstract: The vapors of peppermint oil and two of its major constituents (menthol and menthone), and sweet basil oil and two of its major constituents (linalool and eugenol), were tested against Sclerotinia sclerotiorum (Lib.), Rhizopus stolonifer (Ehrenb. exFr.) Vuill and Mucor sp. (Fisher) in a closed system. These fungi cause deterioration and heavy decay of peach fruit during marketing, shipping and storage. The essential oils, their major individual aroma constituents and blends of the major individual constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(97 citation statements)
references
References 9 publications
9
84
1
3
Order By: Relevance
“…On the other hand, the higher toxicity by fumigant treatment occurs more rapidly because of the direct effect of the essential oil vapors on the fungal mycelia. Some investigators reported that the lipophilic nature of essential oils render them more absorbable by the fungal mycelia than by agar due to the highly lipophilic nature of the fungal mycelia and the high water content of the agar media 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the higher toxicity by fumigant treatment occurs more rapidly because of the direct effect of the essential oil vapors on the fungal mycelia. Some investigators reported that the lipophilic nature of essential oils render them more absorbable by the fungal mycelia than by agar due to the highly lipophilic nature of the fungal mycelia and the high water content of the agar media 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…The volatile phase of essential oil showed a fungistatic action, partially inhibiting the mycelial growth of fungi. Volatile phase of artemisia, peppermint, basil and thyme essential oils were also reported to posses antimicrobial activity against plant pathogenic fungi (Edris & Farrag, 2003;Soylu et al, 2005). Investigators suggested that the antifungal activity resulted from a direct effect of essential oil vapours on fungal mycelium and postulated that the lipophilic nature of essential oils would make possible for them being absorbed by fungal mycelia (Edris & Farrag, 2003;Inouye et al, 2000).…”
Section: Discussmentioning
confidence: 99%
“…It is suggested that the essential oils, with or without surfactants, have fungicidal activities. Menthone and menthol are known as main components of peppermint [14] [15]. These two components are reported to act against C. albicans based on a study on their MICs and MFCs using broth microdilution method [16].…”
Section: Discussionmentioning
confidence: 99%